Soil and Land Use Suveys for Determining Capability in DPAP and DDP Areas in the Country - Shanware, P.G.; Gawande, S.P. (Journal of Soil and Water Conservation, 2022)
The paper deals with the draught prone and desert areas in the country. The approach for development of these areas by providing sound land and water data base is high lighted in this paper. The different kinds of surveys to generate the data base is also described here.